As if God existed religion and liberty in the history of Italy - Viroli, Maurizio (Princeton, N.J. : Princeton University Press, 2012)
Religion and liberty are often thought to be mutual enemies: if religion has a natural ally, it is authoritarianism--not republicanism or democracy. But in this book, Maurizio Viroli, a leading historian of republican political thought, challenges this conventional wisdom. He argues that political emancipation and the defense of political liberty have always required the self-sacrifice of people with religious sentiments and a religious devotion to liberty. This is particularly the case when liberty is threatened by authoritarianism: the staunchest defenders of liberty are those who feel a de
Republics protected by God -- Images of the civil religion -- Republican and monarchical religion -- A religion that instills virtue -- Sacred laws and sacred republics -- Republican religion and religious reform -- A religion to live free -- Within the soul -- The twilight of republican religion -- Without God -- After the revolution -- The new alliance -- Literature and hymns of the religion of liberty -- Apostles and martyrs -- Masters -- Regrets and the quest for new faiths -- Two clashing religions -- In the name of Christ -- Inner liberty -- The religion of liberty -- A religion that instills hope -- The religion of duty -- As if God existed -- Only a god can expel a god -- Leaving life -- Twilight.
Includes bibliographical references (p. ) and index.
Description based on print version record.
Keywords: Liberty -- History; Religion and politics -- Italy -- History; Religion and state -- Italy -- History; POLITICAL SCIENCE / Political Process / General; Electronic books